Real-time macro monitoring and fiscal policy - Eduardo Ley; Florian Misch (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
This paper considers the effects of inaccurate real-time output data on fiscal policy, both with respect to budgetary planning and fiscal surveillance. As newer and better information becomes available, output data available in real time get revised and are likely to conflict with final figures that are only released some years later. By contrast, fiscal policy is inevitably based on real-time figures. The paper develops a simple but comprehensive modeling framework to formalize the linkages between output data revisions and fiscal policy and combines it with a newly compiled dataset from the International Monetary Fund's World Economic Outlook, comprising final and real-time output data for 175 countries, over a period of 17 years. Based on a simulation exercise, it finds that output data revisions alone may significantly undermine the reliability of real-time estimates of the overall and structural fiscal balances, and that output data revisions may result in unplanned and substantial debt accumulation. The paper also shows that there are significant differences across country income groups.
urn:nbn:de:bsz:180-madoc-375222
Keywords: E01; E62; H68; 330; Real-time Output Data; Fiscal Policy; Data Revisions; Public Debt